The Bacillary Postbiotics, Including 2-Undecanone, Suppress the Virulence of Pathogenic Microorganisms - Satish Kumar Rajasekharan; Moshe Shemesh (MDPI AG, 2022)
Secreted molecules from probiotic Bacilli have often been considered potential pharmaceuticals to fight infections caused by bacterial or yeast pathogens. In the present study, we investigated the antagonistic potential of secreted probiotic filtrates (hereafter, postbiotics) derived from Lactobacillus plantarum cells against pathogenic microorganisms, such as Escherichia coli, Staphylococcus aureus, and Candida albicans. We found that the postbiotics mitigate the biofilms of the tested pathogens with no notable effect on their planktonic growth. In addition, the postbiotics suppressed some virulence traits, for instance, the dendrite swarming motility of E. coli and yeast-to-hyphal switch in C. albicans. Further assays with an active constituent produced by the L. plantarum cells-2-undecanone revealed two significant findings: (i) 2-undecanone inhibits C. albicans biofilms and hyphae in vitro and in a Caenorhabditis elegans model, and (ii) it interacts specifically with Gln 58 amino acid residue of hyphal wall protein-1 (Hwp-1) in molecular docking analysis. The results suggest the targeted mode of antagonistic action of 2-undecanone against C. albicans biofilm. In total, the findings of the study depict an appealing strategy to use postbiotics, including specific ketone molecules, produced by L. plantarum for developing novel antibiofilm and anti-hyphal pharmaceuticals.